Effects of restricting energy during the gilt development period on growth and reproduction of lines differing in lean growth rate: responses in reproductive performance and longevity. (26th November 2021) - Johnson, Rodger K; Trenhaile-Grannemann, Melanie D; Moreno, Roman; Ciobanu, Daniel C; Miller, Phillip S
Abstract: Longevity and reproductive performance are economically important traits in the swine industry that are largely influenced by nutrition and other environmental factors. Reproductive performance and longevity through 4 parities was assessed in gilts of 2 genetic lines developed on ad libitum access to feed or restricted to 75% of ad libitum intake. A total of 661 gilts were used in a 2 × 2 factorial with half of the gilts allocated to an ad libitum diet (AL; n = 330), while the other half were energy restricted by 25% (R; n = 331) from 123 to 235 d of age. All gilts were sired by an industry maternal line. Dams of the gilts were from either a Large White (W) by Landrace (L) industry maternal line or Nebraska Selection Line 45X, producing gilts designated as W × L ( n = 355) and L45X ( n = 306), respectively. Daily estrus detection began at 140 d of age to obtain age at puberty (AP). Gilts ( n = 510) were mated on their second or later estrus, beginning at 240 d of age. Sow weight and backfat were recorded at 110 d of gestation and weaning of each parity. Number of live-born, stillborn, and mummified pigs per litter and piglet birth and weaning weights were recorded through 4 parities. More L45X than W × L and more AL than R gilts reached puberty by 230 d of age ( P < 0.01). Dietary treatment did not affect probability to produce parities 1 to 4 or any litter trait analyzed. The L45X females tended to be more likely to produce parities 1 ( P < 0.08) and 3 ( P < 0.06), while W × L had heavier litters at birth ( P < 0.01) and weaning ( P = 0.01). Treatment by parity interactions ( P < 0.01) existed for weight and backfat prior to farrowing and backfat at weaning, and weight at weaning exhibited a line by treatment by parity interaction ( P = 0.04) as R sows had lower weights and backfats in earlier parities, but caught up to AL sows in later parities. A treatment by parity interaction ( P < 0.01) was also present for backfat loss from farrowing to weaning as R gilts lost less backfat than AL in parities 1 and 2, but more in parities 3 and 4. No significant differences were detected between lines or treatments for lifetime production traits. The populations of pigs and data presented here provide a framework for a diverse array of further studies. Alternative approaches to restrict energy have been assessed in addition to methods of marker-assisted and genomic selection for improvement of litter size and sow longevity.